Thermodynamic characterization of phthalocyanine–human serum albumin interaction. Issue 5 (2011) - Dezhampanah Dezhampanah, Hamid Hamid; Bordbar Bordbar, Abdol Khalegh Abdol Khalegh; Farshad Farshad, Shamim Shamim
Abstract : The thermodynamic of the binding of nickel (II) tetrasulfonated phthalocyanine anion [Ni(tspc) 4– ], to human serum albumin (HSA) was investigated in 5 mM aqueous phosphate buffer of pH 7.40 at 25 ° C using optical absorption spectroscopy. The results show that [Ni(tspc) 4– ] does not have any affinity for aggregation due to increasing of salt concentration and exists as monomers even in homogeneous aqueous solutions of high ionic strengths (more than 2 M NaCl). The binding constant ( K ) was obtained by analysis of optical absorption spectra of mentioned complex at various HSA concentrations using SQUAD software. The value of K was estimated to be 4.89×10 5 ±0.03 (M –1 ) at 25 ° C. The thermodynamic parameters were calculated by van't Hoff equation. The enthalpy and entropy changes were 28.08 kJ/mol and 203.09 J/(mol · K) at 25 ° C, respectively. The results indicate that the binding is mainly entropy driven and the enthalpy is unfavorable for it, the hydrophobic forces thus playing a major role in the binding process.